KONTRADIKSI PERKAWINAN PELAKU DENGAN KORBAN PERKOSAAN DALAM PERSPEKTIF PERTANGGUNGJAWABAN PIDANA - Arinal Achsana (2023)
The practice of marrying perpetrators and victims of rape is often carried out in Indonesian society as a way to resolve rape cases and as a form of responsibility by the perpetrator towards the victim. The labeling of rape victims and the difficulty for victims to obtain justice lead many rape victims to choose to accept this form of responsibility. This study aims to understand the contradiction of marrying perpetrators and victims of rape and how perpetrators should be held criminally accountable for their actions. The study is conducted using a normative juridical method, examining legislation regarding rape and linking it to societal practices in resolving rape cases. The research findings reveal that marrying perpetrators and victims of rape leads to further suffering for the victims and serves as an excuse for the perpetrators to escape legal consequences. This marriage practice contradicts the concept of criminal accountability and constitutes a phenomenon of legal violation. The practice of marrying perpetrators and victims of rape violates Article 10 paragraph (2) of the Law on Criminal Acts of Sexual Violence. Perpetrators of rape should be held criminally accountable as stipulated in Article 285 of the Criminal Code and Article 6 letter c of the Law on Criminal Acts of Sexual Violence. Keywords: Rape, Contradiction, Criminal responsibility, Forced Marriage